Challenges of Using AI Writing Tools in the Thesis Writing Process: A Study on Undergraduate English Education Students at Universitas Muhammadiyah Bengkulu - Ivan Achmad Nurcholis; Revo Aditama Febrian (Teaching English and Language Learning English Journal, 2025)
The use of Artificial Intelligence (AI) writing tools such as ChatGPT, Grammarly, and Quillbot has rapidly expanded in academic contexts, particularly in higher education. While these tools offer significant benefits in assisting students with grammar correction, paraphrasing, and idea generation, they also pose critical challenges related to dependency, originality, academic integrity, and writing quality. This study explores the challenges experienced by undergraduate English Education students at Universitas Muhammadiyah Bengkulu when using AI writing tools during their thesis writing process, along with the strategies adopted to overcome them. Employing a descriptive qualitative approach, data were collected from 22 final-year students through open-ended questionnaires and semi-structured interviews. Thematic analysis revealed five key challenges: dependency on AI tools, issues of originality and plagiarism, difficulties in maintaining academic writing conventions, technical and conceptual limitations of AI tools, and fluctuating confidence in writing. To address these challenges, students applied self-regulation, consulted supervisors, used plagiarism checkers, paraphrased content manually, and improved independent writing skills. The study concludes that AI tools can effectively support thesis writing when used ethically and critically, supported by institutional guidance and academic supervision.   Keywords : AI Writing Tools, Academic Writing, Thesis Writing, EFL Students, Challenges